BURDENSOME END-OF-LIFE (EOL) TRANSITIONS AMONG FRAIL OLDER ADULTS WITH ADVANCED CANCER. (11th November 2018) - Lage, D; Lee, Y; Mitchell, S; Temel, J; El-Jawahri, A; Berry, S
Abstract: Older adults with advanced cancer residing in nursing homes (NHs) are a vulnerable, understudied population. We described these patients' clinical characteristics and burdensome EOL care transitions. We conducted retrospective analysis of deceased older adults (>65) with advanced solid tumors residing in NHs. Medicare data were linked with geriatric assessments via the Minimum Data Set. Clinical characteristics were measured within 90 days of death. Per prior studies, we defined a burdensome transition as two or more hospitalizations or any intensive care unit admission in the last 90 days of life. We included 34, 670 patients with advanced solid tumors. Many residents had comorbid congestive heart failure (CHF) (29.3%), chronic obstructive pulmonary disease (COPD) (34.1%), and diabetes (35.0%). 53.8% had moderate or severe cognitive impairment, 66.5% were dependent in all ADLs, and 55.4% used hospice. Overall, 36.0% of patients experienced a burdensome transition at the EOL, and burdensome transitions were more common for patients who did not receive hospice (45.3% vs. 28.6%, p<0.01). In adjusted analyses, the following characteristics were associated with higher risk of burdensome transition: female sex (OR 1.2, P<0.001), CHF (OR 1.56, P<0.001), COPD (OR 1.3, P<0.001), diabetes (OR 1.3, P<0.001), full dependence in ADLs (OR 1.9, P<0.001), and receipt of chemotherapy in the last 90 days of life (OR 1.7, P<0.001). Although NH residents with advanced cancer have substantial comorbidities, cognitive deficits, and functional impairments, over a third experienced a burdensome transition at the EOL. Interventions are critically needed to reduce burdensome EOL transitions in this vulnerable population.